Pemanfaatan lubang biopori sebagai resapan air hujan dan kompos alami di wilayah Kelurahan Penurunan Kota Bengkulu - Andriana Marwanto; Mualim Mualim (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2021)
Most of the rainwater that falls to the earth cannot seep directly into the ground and eventually becomes runoff or what is often called surface water. Rainwater runoff that is not handled properly will cause various problems for the community, especially flooding. The negative impact of changing or losing catchment areas is that they cannot withstand the flow rate of water due to rainfall, causing stagnation of water or even flooding. Flood hazard in residential areas often occurs due to changes in land use from infiltration areas to watertight areas. Solutions that can be used to overcome flood problems, especially for dense residential areas or those with minimal rainwater infiltration, can be done by using biopore technology. The method used in this community service activity is to provide community empowerment regarding the use of biopore holes as rainwater infiltration and natural compost with demonstrations and practice of making biopore holes. The result of this community service activity is that the activity participants are able to make biopore holes as rainwater infiltration and natural compost which can then make biopore holes around the home page and share information and skills with other communities so that they can reduce standing water when it rains and can take advantage of compost management. Key words: biopore holes, infiltration water and compost